Transformasi Oragnisasi Layanan Kemanusiaan Berbasis Agama: Studi Komparasi Lembaga Zakat Korporat YBM BRILiaN, BSI Maslahat, dan YBM PLN - Noviawan, Dwi Iqbal; Machdum, Sari Viciawati; Haidlir, Banu Muhammad (Riviera Publishing, 2025)
Since the ebactment of Law No. 38 of 1999, zakat management institutions (Lembaga Amil Zakat/LAZ) have evolved beyond their traditional role as religious fund distributors to become faith-based human service organizations that are increasingly adaptive to social challenges and demands for professionalism. This study aims to analyze the organizational transformation undertaken by three corporate-affiliated zakat institutions YBM BRILiaN, BSI Maslahat, and YBM PLN through the lens of the political-economy perspective by Wamsley and Zald (1973) and the internal-external factor framework of Kettner (2002). The findings reveal that the organizational transformations in these institutions are responses to external pressures such as parent company policies, government regulations, public expectations, and the rapid shift toward digitalization. Internally, these changes are driven by improvements in human resource capacity, organizational restructuring, and cultural renewal. Although the three institutions share similar religious foundations and social missions, their transformation strategies differ: YBM BRILiaN focuses on organizational efficiency and strengthening community-based programs, BSI Maslahat moves toward zakat institutionalization through a social holding model, while YBM PLN demonstrates the most comprehensive transformation by integrating digital innovation, volunteer empowerment, and decentralized decision-making. This study contributes to a deeper understanding of the transformation of faith-based zakat organizations in the context of modernity and corporate alignment.